'And the Oscar Goes to… Daybreak in Udi': Understanding Late Colonial Community Development and its Legacy through Film. Issue 5 (18th August 2014) - Page, Ben; Chhachhi, Amrita
ABSTRACT This article analyses the 1949 film Daybreak in Udi and the influential ideas of its 'star' Edward Rowland Chadwick, a District Officer, with a view to understanding the legacy of the colonial policy of Community Development in Eastern Nigeria and Cameroon. The film, which is freely available online, follows an African community using 'self‐help' methods to construct a rural maternity home. It helps visualize the colonial practices of 'mass education' and 'community betterment' but is not just a drama‐documentary: it is also an argument in favour of community development. The article argues that Chadwick's ideas had a profound influence within the region where he worked, and that colonial community development more generally provides a key source for 'participatory development'. The film also discloses a late colonial 'socio‐geographical imaginary', articulated through a hierarchy of specific social categories (administrative officers, teachers, peasants, elders, women and troublemakers), spatial locations (urban, rural) and the distinctions between them (modern/reactionary, leader/worker, audible/silent). The article shows that colonial community development not only played an important role in fixing these categories within subsequent development thinking, but that it also ran up against one of the ongoing paradoxes of 'self‐help development', namely that it usually requires an outsider.